Meretas Jalan Kritis: Privatisasi Pendidikan di Perguruan Tinggi Negeri Badan Hukum dalam Lensa Kantian - Jepri Utomo; Syamsu A. Kamaruddin; Arlin Adam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to apply Immanuel Kant's ethical framework to examine the moral implications of the privatization of education on State Legal Entity Higher Education Institutions. The study identifies the primary emphasis of ethical analysis on structural changes, tuition fee increases, resource allocation, and stakeholders' perspectives using a literature review approach. Inconsistencies between education privatization policies and the values of universality, fair treatment, and moral responsibility are highlighted by research utilizing the Kantian framework. The research findings indicate that the PTNBH's policy to privatize education raises ethical issues, particularly related to resource allocation, accessibility, and the moral obligations of the institution. In conclusion, there are serious ethical consequences to the privatization of PTNBH education Keywords: Critical Pathfinding, Education Privatization, Kantian Lens, Higher Education Institutions State Legal Entity